Expressivist to the core: Metaaesthetic subjectivism is stable and robust. (April 2020) - Rabb, Nathaniel; Han, Alex; Nebeker, Lucy; Winner, Ellen
Abstract: Two common observations about aesthetics are in tension: that people generally consider aesthetic judgments subjective, and that people generally behave like objectivists (arguing over judgments, making choices based on judgments of trusted critics, rejecting strong assertions of aesthetic equivalence). This tension would be resolved if the first observation turned out to be false—if people endorsed subjectivism weakly, flexibly, or rarely. We tested whether people can be pushed to endorse objectivism under certain circumstances. Across a large sample ( N = 588), aesthetic subjectivism proved consistent and robust to experimental manipulations. Even judgments that reflected participants' own evaluations of artworks were considered just as subjective as judgments directly opposed to their personal evaluations. We conclude that the apparent tension can be explained by the philosophical position of expressivism and discuss expressivism's prospects as a framework for understanding aesthetic judgment.